A Novel Design of an Inner Rotor for Optimizing the Air-Gap Magnetic Field of Hollow-Cup Motors - Jinji Sun; Jianyi Ren; Haoxi Sun (Machines, 2022)
In order to obtain a high power density, spacecraft usually use hollow-cup motors with trapezoidal air-gap magnetic field waveforms. However, due to structural issues, the hollow-cup motor has the problem that the waveform of the air-gap magnetic field is inconsistent with the ideal trapezoidal waveform, which causes torque ripples. In order to reduce torque ripples, the existing method only changes the structure of PMs; the changed PMs are difficult to magnetize and manufacture, which causes the air-gap magnetic field waveform to be unsuitable as the ideal waveform. This paper proposes a novel design of an inner rotor of a hollow-cup motor with an eccentric inner rotor based on the characteristics that the hollow-cup motor has inner and outer rotors and the two rotors rotate synchronously during operation. First, the influencing factors of the air-gap magnetic field are analyzed and the mathematical model of the eccentric inner rotor is established. Then, an eccentric model is established by finite element analysis, which proves that the eccentricity of the inner rotor can make the air-gap magnetic field waveform closer to the ideal trapezoid. Finally, a prototype based on the optimal eccentricity value is developed, verifying the effectiveness of the novel design of the inner rotor.